Spatiotemporal variations in microbial diversity across the three domains of life in a tropical thalassohaline lake (Dziani Dzaha, Mayotte Island). Issue 23 (22nd November 2018) - Hugoni, Mylène; Escalas, Arthur; Bernard, Cécile; Nicolas, Sébastien; Jézéquel, Didier; Vazzoler, Fanny; Sarazin, Gerard; Leboulanger, Christophe; Bouvy, Marc; Got, Patrice; Ader, Magali; Troussellier, Marc; et al.
Abstract: Thalassohaline ecosystems are hypersaline environments originating from seawater in which sodium chloride is the most abundant salt and the pH is alkaline. Studies focusing on microbial diversity in thalassohaline lakes are still scarce compared with those on athalassohaline lakes such as soda lakes that have no marine origin. In this work, we investigated multiple facets of bacterial, archaeal and eukaryotic diversity in the thalassohaline Lake Dziani Dzaha using a metabarcoding approach. We showed that bacterial and archaeal diversity were mainly affected by contrasting physicochemical conditions retrieved at different depths. While photosynthetic microorganisms were dominant in surface layers, chemotrophic phyla (Firmicutes or Bacteroidetes) and archaeal methanogens dominated deeper layers. In contrast, eukaryotic diversity was constant regardless of depth and was affected by seasonality. A detailed focus on eukaryotic communities showed that this constant diversity profile was the consequence of the high predominance of Picocystis salinarum, while nondominant eukaryotic groups displayed seasonal diversity turnover. Altogether, our results provided an extensive description of the diversity of the three domains of life in an unexplored extreme environment and showed clear differences in the responses of prokaryotic and eukaryotic communities to environmental conditions.